La Implementación como Delito Penal al ‘Revenge Porn’ o Venganza Digital - Granda Orellana, Stefany Lisseth (2024)
This research work entitled "THE IMPLEMENTATION OF 'REVENGE PORN' OR DIGITAL REVENGE AS A CRIMINAL OFFENSE", is carried out because this social problem violates several of the Freedom Rights, which are recognized and guaranteed in the Constitution of the Republic of Ecuador, in its article 66, which are the following: Right to honor and good name; Right to personal and family privacy; Personal integrity right; Right to equality and non-discrimination. Since the crime of revenge porn or digital revenge is unlawful conduct, which is characterized by the non-consensual dissemination of explicit sexual content of a person, disseminated with the purpose of harming, humiliating, or taking revenge on someone, as was well seen With the advent of technology, it would also drag with it countless crimes, where one of the least regulated and that causes the most damage in a person's personal and professional life is Revenge Porn or Digital Revenge. It is fact, to carry out the implementation and recognition of the crime of revenge porn or digital revenge, since it is an abrupt conduct, which with the passing of time expands massively when seeing that there is no specific norm that regulates it, it is It is also important to be able to develop and recognize new criminal types, to implement them before they surprise us, as this criminal modality has already been doing, which is why we must implement this new unlawful conduct just as foreign legislation already does, such as Mexico, Argentina and Italy. Thus, my present work aims to carry out a doctrinal and legal analysis in relation to the implementation in the Comprehensive Organic Criminal Code as a crime of "revenge porn" or digital revenge.